COLOR CHANGES OF POST-DEBONDING WHITE SPOT LESION AFTER MICROABRASION TECHNIQUE WITH FLUORIDE AND CASEIN PHOSPHOPEPTIDE-AMORPHOUS CALCIUM PHOSPHATE APPLICATION - Angriawan, Irene Pratami; Anggani, Haru Setyo; Ismah, Nada (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The prevalence of enamel demineralization among patients after orthodontic treatment is about 50%, which begins with the formation of white spot lesions. The presence of these lesions causes esthetic problems. The aim of this study was to quantify the color changes in post-debonding white spot lesions after microabrasion technique with fluoride and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) application. Materials and Methods: This study used 42 first premolar teeth that had been extracted, then were soaked for 96 h in a demineralization solution (pH 4, 37Â°C) to form an artificial white spot lesions. Samples were randomly divided into three treatment groups (n=14): (A) Microabrasion technique only; (B) microabrasion technique with 10% CPP-ACP paste application; and (C) microabrasion technique with 1.23% APF gel application. All groups were assigned to pH cycling for 10 days. The color change was determined using spectrophotometer at 3 different time points, which were measured before and after production of the artificial white spot lesions, and after the artificial white spot lesions were treated. Results: This study showed that there was a significant difference in the color of the artificial white spot lesions after microabrasion technique with CPP-ACP application. Conclusion: Microabrasion technique with CPP-ACP application was giving better result in changing the color of white spot lesions than only microabrasion technique and microabrasion technique with fluoride application.